BEBERAPA CATATAN TENTANG FONOLOGI BAHASA KAMORORAGAM AI’AOWE - Christ Fautngil (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe the phonological aspects of the Ai’aowe variety in the Kamoro language as one of the Papuan languages in Mimika Regency. It employed the qualitative descriptive method using the structural approach. The findings are as follows. First, the Ai’aowe variety in the Kamoro language has more vowels than consonants. There are ten vowels, namely /i/, /ii/, /e/, /ee/, /a/, /aa/, /u/, /uu/, /o/, /oo/ and eight consonants, namely /p/, /m/, /t/, /n/, /r/, /w/, /y/, /?/. Second, in this language there are only open syllables, so that there are only two types of syllable patterns, namely V and CV. The stress falls on the final syllable. Third, in the morphophonemic process, a verbal change is influenced by the person, tense, and aspect, making a word longer with more syllables. Fourth, the Ai’aowe variety in the Kamoro language is influenced by outside languages, including Indonesian, so that there is a tendency for nonnative phonemes to exist.